High-level synthesis of large digital systems based on precedence bipartite model - Shen Zhaoxuan. (2009)
During recent years, high level synthesis has emerged as one of the most exciting and challenging areas in design automation. Ever increasing microelectronics technology and market competition drive the digital systems more and more complex. Increasingly large scale of digital circuits, more and more complex design requirements and objectives are all invoked into high level design. Tradeoffs of large design space exploration and complex objective optimization become crucial problems in high-level synthesis.